Lingkaran Kehidupan dalam Penciptaan Seni Lukis - Yugus, Anak Agung Gde (CITA KARA : JURNAL PENCIPTAAN DAN PENGKAJIAN SENI MURNI, 2021)
Life is something that is very complex and unique, which is always running, rotating, and changing according to its nature. It is undeniable that everyone will experience a life cycle that is based on the concept of Rwa Bhineda, namely life-death, joy-sorrow, sadness-happy, health-sickness, and others. Based on the circle of life, abstract paintings will be created embodied in symbols full of meaning and deep meaning. The values of life in society with all of its problems will be expressed into a visual art work as an artifact that can summarize all the various events of the world. The creation of this work is expected not only to function as mere visual artifacts, but to have a deep value that life will always rotate according to its nature. The task of humans is how to interpret life so that life can be useful and in accordance with its true purpose. With line strokes, color strokes, and the composition of the fields and spaces embodied in the symbols, it is hoped that they will enlighten all people to interpret life by accepting all the natures that occur while still trying to fight all existing problems.